Enhancing Digital Health Services in ASEAN Countries: Comparison of Indonesia, Singapore, and Thailand - Milla Herdayati; Popy Yuniar (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2026)
Digital health is transforming healthcare globally, with ASEAN nations like Singapore, Thailand, and Indonesia showing diverse progress. This study analyzes and compares their digital health services to pinpoint best practices and improvement areas. Employing a mixed-methods approach involving literature reviews, policy analysis, and data gathering on infrastructure and service adoption from government and academic sources, the research focuses on governance, investment, infrastructure, and service uptake. Findings reveal Singapore as a digital health frontrunner due to its strong governance, substantial investment, advanced infrastructure, and high adoption. Thailand shows progress but grapples with decentralized governance and urban-rural divides. Indonesia's developing sector faces fragmented governance, limited investment, and infrastructure deficits. The study underscores the importance of centralized governance and robust investment for successful digital health implementation, highlighting Singapore's cohesive strategy as a beneficial model. Thailand and Indonesia need to enhance policy consistency and infrastructure development to improve the effectiveness of digital health services in ASEAN. Ultimately, advancing digital health in ASEAN necessitates a comprehensive strategy encompassing strengthened governance, increased investment, better infrastructure, and greater public awareness, drawing lessons from successful models to improve regional healthcare access and quality.